PENERAPAN METODE FORECAST DALAM MENYUSUN ANGGARAN PENJUALAN PADA SALES PARTNER PT. COCA - COLA AMATIL INDONESIA CABANG KEBUMEN - Retnosari, Retnosari (P4M STIE Putra Bangsa, 2015)
The purpose of budget formulation, budget function, the benefits of budgeting, the weaknesses of the budget, the types of budgets, understanding budget of sales, factors which mempegaruhi sales budgeting, understanding the forecast sales, techniques contained in the sales forecast, after an evaluation and finally gave advice as input to the company for consideration. Data analysis technique is to include sales data in 2013 and then put into the formula, and then comparing the sales budget for 2014 that has been made with the realization penjulan 2014. The comparison is used to look for the differences that will be incorporated into the formula, using the method of calculation The forecast can know which method is most closely compliance with the conditions of the company. Results of the study showed that the company must perform sales budget and to choose the method of budget according to the conditions of the company is using the least squares method, because this method is closer to the data processed Sales Partner PT. Coca-Cola Amatil Indonesia. Keywords: Budget, Budget Sales, Sales Forecast.